Prototipe Sistem Informasi Geografis Fasilitas Kesehatan di Kota Cirebon Berbasis Web - Dani Rahardjo; W Warkim (Maranatha University Press, 2015)
In the development of health need the data and information system that is integrated with both the development process so that health facilities can be optimized and the right target. One information system that can be used in the development of health facilities in the city of Cirebon is a geographic information system (GIS). And one of the software to build applications GIS is an Arcview and AlovMap. ArcView software is one of the software (tools) GIS and mapping was developed by ESRI (Environmental Systems Research Institute, Inc). ArcView has the ability to do data visualization, data exploration, the query (both spatial and non-database spatial), analyze the data geographically, and so forth. And AlovMap (including open source software) is a portable application WebGIS Java-based publication that is used to Raster and vector data on the Internet. Excess geographic information system facilities in the city of Cirebon AlovMap use is open source and are cheaper and have the ability to support the visualization of information in decision making. This system can produce a map of the output of these pharmacies, laboratories and hospitals. Utilization of GIS for health facilities that was built is extraordinary in integrating between science, technology and health.Â Keywordsâ€” Arcview, Alowmap, Geographic information system, Health of facilities, Overlay, Shortest path.